A study on the awareness of Ex-Gratia compensation scheme among Socso employees in Johor / Fatin Farhana Zameri - Zameri, Fatin Farhana (Faculty of Business and Management, 2011)
The establishment of Ex-Gratia is a good effort by the government to look after the welfare of its workers in terms of financial compensation for occupational related injuries and diseases. The scheme should be treated as employer’s liability similar to those as SOCSO schemes rather than an incentive to government servant. Ex-Gratia Compensation Scheme existence still not being aware by public majority especially government servant. The factors are the lack of promotion and knowledge to attract people to aware of the services. Therefore, the research is conduct to study the level of awareness towards this scheme among SOCSO employees in Johor.